Synonymous Mutations of Porcine Igf1r Extracellular Domain Affect Differentiation and Mineralization in MC3T3-E1 Cells - Wang, Chunli; Wang, Siyao; Liu, Songcai; Cheng, Yunyun; Geng, Hongwei; Yang, Rui; Feng, Tianqi; Lu, Guanhong; Sun, Xiaotong; Song, Jie; Hao, Linlin (Frontiers in Cell and Developmental Biology, 2020)
Owing to the wide application of miniature pigs in biomedicine, the formation mechanism of its short stature must be elucidated. The insulin-like growth factor 1 receptor (IGF-1R), which receives signals through the extracellular domain (ECD) binding with ligands, is crucial in regulating cell growth and bone matrix mineralization. In this study, two haplotypes of Igf1r with four synonymous mutations in the coding sequences of IGF-1R ECD between large pigs (LP) and Bama pigs (BM) were stably expressed in the Igf1r-knockout MC3T3-E1 cells and named as MC3T3-LP cells (LP group) and MC3T3-BM cells (BM group), respectively. IGF-1R expression was lower in the BM group than in the LP group both in terms of transcription and translation levels, and IGF-1R expression inhibited cell proliferation. In addition, IGF-1R expression in the BM group promoted early-stage differentiation but delayed late-stage differentiation, which not only suppressed the expression of bone-related factors but also reduced alkaline phosphatase activity and calcium deposition. Moreover, different haplotypes of Igf1r changed the stability and conformation of the protein, further affecting the binding with IGF-1. Our data indicated that the four synonymous mutations of IGF1R ECD encoded by affect gene transcription and translation, thereby further leading to differences in the downstream pathways and functional changes of osteoblasts.